An evaluation of the interactive-activation model using masked partial-word priming. - Perry JR; Lupker SJ; Davis CJ (Language & Cognitive Processes, 2008)
Predictions from Davis and Lupker's (2006) version of the interactive-activation model (McClelland & Rumelhart, 1981) were tested in four masked priming lexical decision experiments. Ambiguous partial-word primes (i.e., ho#se resembles HOUSE and HORSE) preceded word targets with few neighbours (low-N) or many neighbours (high-N) when the word/nonword discrimination was either easy (Experiment 1A) or difficult (Experiment 1B). In a second experiment, unambiguous partial-word primes (i.e., cl#ff resembles only CLIFF) preceded hermit (i.e., words with no neighbours), low-N, or high-N word targets when the word/nonword discrimination was either easy (Experiment 2A) or difficult (Experiment 2B). The model's predictions are supported by the results for the ambiguous primes, but not by the results for the unambiguous primes, particularly when hermit targets are used. A revised definition of the orthographic neighbourhood of a word and/or different assumptions about the impact of frequency on lexical representations would improve the model's ability to account for the data.